2021
DOI: 10.1177/1049731520984844
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Participation in Decision Making From Child Welfare Workers’ Perspectives: A Systematic Review

Abstract: This article explores child welfare workers’ experiences of children’s participation in decision making in the child protection system. The systematic review follows the principles of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement and includes 12 peer-reviewed articles published in academic journals from 2009 to 2019. Findings indicate that children’s participation in decision making is generally limited or nonexistent. The age of the child is an important determining factor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…The extent to which children are seen, heard and authentically represented at the CPC is mediated by a complex and nuanced interplay of individual (child and professional), organizational and structural factors (Bastian, 2020; Collins, 2018; Ferguson, 2016; Kosher & Ben‐Arieh, 2020; Toros, 2021; Vis et al, 2012) that are located within a child protection system that endeavours to act in the child's best interests and to promote participation within competing discourses of child protection. The production of an organization's frame of reality is founded on organizational discourses, which in turn serve to define and regulate the day‐to‐day local practices created through social relations.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which children are seen, heard and authentically represented at the CPC is mediated by a complex and nuanced interplay of individual (child and professional), organizational and structural factors (Bastian, 2020; Collins, 2018; Ferguson, 2016; Kosher & Ben‐Arieh, 2020; Toros, 2021; Vis et al, 2012) that are located within a child protection system that endeavours to act in the child's best interests and to promote participation within competing discourses of child protection. The production of an organization's frame of reality is founded on organizational discourses, which in turn serve to define and regulate the day‐to‐day local practices created through social relations.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-synthesis, we summarize children’s perspectives on their participation in foster care processes and in particular their (non-) participation in the removal from home, foster family processes, and placement breakdown. The findings of this meta-synthesis will be useful to policy makers, who are increasingly requested to incorporate children’s voices into decision-making [ 16 , 24 , 25 ], and practitioners, who need to consider the nuances of when and how to include children’s voices in practice and decision-making [ 26 ]. The inclusion of children’s voices has a number of benefits to children, practitioners, and policy makers, such as affording children their inherent rights to participate, empowering children and reducing their confusion regarding services, and improving service delivery through more tailored, responsive services [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this meta-synthesis will be useful to policy makers, who are increasingly requested to incorporate children’s voices into decision-making [ 16 , 24 , 25 ], and practitioners, who need to consider the nuances of when and how to include children’s voices in practice and decision-making [ 26 ]. The inclusion of children’s voices has a number of benefits to children, practitioners, and policy makers, such as affording children their inherent rights to participate, empowering children and reducing their confusion regarding services, and improving service delivery through more tailored, responsive services [ 24 , 26 , 27 ]. As the authors of one review note, children’s “participation has both intrinsic (dignity and self-worth in terms of expressing views to influence decisions about their lives) and instrumental (policy and better outcomes for children in terms of supportive relationships with their workers and positive experiences at school and in CPS [children protection services]) value” [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review found that while child welfare workers valued children's participation, children had limited involvement in decision-making, age influenced participation opportunities and workers considered the potential harm of participation (Toros, 2021a). Practitioners make different decisions about participation depending on their interpretations of children's maturity and age (Toros, 2021a). We need to find ways to engage all children rather than assessing their capacity to participate in adult-designed processes (Toros, 2021b).…”
Section: Participation In Child Protectionmentioning
confidence: 99%